Soil seed bank formation during early revegetation of areas affected by mining in a tropical rain forest of Chocó, Colombia - Valois-Cuesta, Hamleth; Martínez-Ruiz, Carolina; Urrutia-Rivas, Yorley (Revista de Biología Tropical, 2017)
Mining is one of the main economic activities in many tropical regions and is the cause of devastation of large areas of natural tropical forests. The knowledge of the regenerative potential of mining disturbed areas provides valuable information for their ecological restoration. The aim of this study was to evaluate the effect of age of abandonment of mines and their distance from the adjacent forest, on the formation of soil seed bank in abandoned mines in the San Juan, Chocó, Colombia. To do this, we determined the abundance and species composition of the soil seed bank, and the dynamics of seed rain in mines of different cessation period of mining activity (6 and 15 years), and at different distances from the adjacent forest matrix (50 and 100 m). Seed rain was composed by five species of plants with anemocorous dispersion, and was more abundant in the mine of 6 years than in the mine of 15 years. There were no significant differences in the number of seeds collected at 50 m and 100 m from the adjacent forest. The soil seed bank was represented by eight species: two with anemocorous dispersion (common among the seed rain species) and the rest with zoochorous dispersion. The abundance of seeds in the soil did not vary with the age of the mine, but was higher at close distances to the forest edge than far away. During the early revegetation, the formation of the soil seed bank in the mines seems to be related to their proximity to other disturbed areas, rather than their proximity to the adjacent forest or the cessation activity period of mines. Therefore, the establishment of artificial perches or the maintenance of isolated trees in the abandoned mines could favour the arrival of bird-dispersed seeds at mines. However, since the soil seed bank can be significantly affected by the high rainfall in the study area, more studies are needed to evaluate management actions to encourage soil seed bank formation in mines of high-rainfall environments in the Chocó region.